Contribution to the study of marine harpacticoid fauna (Crustacea, Copepoda) of Iceland ... - Apostolov, Apostol (Zenodo, 2014)
Apostolov, Apostol (2014): Contribution to the study of marine harpacticoid fauna (Crustacea, Copepoda) of Iceland. ZooNotes 62 (62): 1-5, DOI: 10.5281/zenodo.8298375 ...